An evaluation of osteoarthrosis in specific anatomic locations of the canine stifle joint treated with tibial plateau leveling osteotomy and tibial tuberosity advancement - S. Pinna; C. Tassani (The Veterinary Journal, 2026)

A new catfish species of Microcambeva Costa & Bockmann, 1994 ( S iluriformes: T richomycteridae) from southern Brazil, with a redescription of M. ribeirae Costa, Lima & Bizerril, 2004 - Lucas S. de Medeiros; Igor C. A. Souto‐Santos; Paulo A. Buckup; Juliano Ferrer; Vinicius J. C. Reis; Mario de Pinna; Sergio M. Q. Lima (Journal of Fish Biology, 2026)
Among the few species of Microcambeva reported as occurring in more than one hydrographic basin, M. ribeirae has been previously listed from both the Ribeira de Iguape and the Guaraqueçaba basins. However, morphological and molecular analyses revealed that the specimens from Guaraqueçaba represent a new species, which is described in this study. Therefore, the distribution of M . ribeirae is restricted to the Ribeira de Iguape basin, and this taxon is redescribed. The new species is the southernmost record of the genus and is diagnosed among congeners by the T‐shaped dark blotch in the dorsal portion of the head in preserved specimens. It is distinguished from most congeners, except for M. bendego and M. ribeirae , by the lack of a filamentous first pectoral‐fin ray. Distinguished from the latter species by having only five pre‐caudal vertebrae, the tip of the hyomandibula reaching the vertical through the anterior tip of the preopercle, and the last anal‐fin ray branched. Molecular analysis of the cytochrome c oxidase subunit I ( cox1 ) mitochondrial gene including most species of Microcambeva (except M. draco ) supports the close relationship of the new species with M. ribeirae . The two species are nonetheless genetically different, with a 2.2% molecular distance. The conservation status and biogeography of the new species and of M. ribeirae are discussed.

Asymmetries challenging global biodiversity sciences - Leandro O. Salles; Hussam Zaher; Marcos Tavares; Mario C. C. de Pinna; Rosane G. Collevatti; Krister T. Smith; Diego Pol; Hongyu Yi; Nancy B. Simmons; Christopher J. Tribe; Joaquin Arroyo-Cabrales; Nour-Eddine Jalil; et al. (Systematics and Biodiversity, 2026)

Application of droplet digital PCR for the detection of fish DNA in food products - S. Cau; B. Soro; R. Melillo; G. Piras; S. Salza; T. Tedde; F. Pinna; B. Vodret; C. Spanu (Food Research International, 2025)

Lateritic Cenozoic paleoenvironmental and paleoclimatic conditions in the Central Amazon basin, Brazil, inferred from mineralogy, geochemistry and geochronology - C. Ansart; D. Guinoiseau; C. Quantin; D. Calmels; C. Gautheron; P. Agrinier; J. Bouchez; Z. Fekiacova; R. Pinna-Jamme; D. Demri; E. Balan; B. Heller; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

How does cruciate ligament rupture treatment affect range of motion in dogs? - S. Pinna; M. Di Benedetto; C. Tassani (The Veterinary Journal, 2024)

Nutritional management of hyperlipaemia in a jenny: a brief report - S. Morrone; S. Sechi; C. Carta; A. Senes; R. Cocco; M. L. Pinna Parpaglia; E. Sanna Passino; M. G. Cappai (Veterinary Research Communications, 2024)
An adult jenny (5-years-old, non-pregnant) was presented to the Veterinary Teaching Hospital (VTH) of the University of Sassari, with a recent history of appetite loss, extreme underweight condition and reluctance to move. On physical inspection, emaciation [body condition score, BCS: 3/9], muscular waste [muscular condition score, MCS: 1/5], loose/running faeces [faecal score, FS: 2/8], and a general state of mild dehydration were found. Blood analyses outlined a general undernourishment condition [circulating albumins, ALB: 17.6 g/L (21.6–31.6 g/L)] with underlying systemic inflammatory profile and moderate increase in circulating enzymes to explore liver function [aspartate amino-transferase, AST: 657 u/L (279–430 u/L); alanine amino-transferase ALT: 60 u/L (5–14 u/L); gamma-glutamyl-transferase, γ-GT: 87 IU/L (14–69 IU/L); total bilirubin close to the upper limit, TB: 0.20 mg/dL(0.07–0.21 mg/dL)]and hyperlipaemia [TG: 8.70 mmol/L (0.60–2.87 mmol/L)], following fat depots mobilisation, with total cholesterol closed to the lower limit of the physiological range. Hyper-phosphataemia was linked to haemolytic anaemia [P:1.81 mmol/L (0.77–1.39 mmol/L) and red blood cells, RBC: 4.14 10 12 /L (4.40–7.10 10 12 )] aligned with the TB to the upper limit. On ultrasound abdominal imaging, enlarged and hyper-echogenic liver was observed. Based on the clinical evaluation, a condition of hepatic lipidosis was diagnosed, requiring dedicated nutritional treatment to solve the extreme emaciation along with the metabolic disorder in support of medical therapy. A two-step feeding protocol was planned to support treatments aiming at immediate re-hydration (Ringer lactate solution 2 ml/kg/8 h). The nutritional objectives were meant at first to restart the voluntary feed intake. Gradual increasing energy provision through a palatable hay-based diet was planned to cover one fourth of daily metabolizable energy requirement calculated on the expected metabolic weight, adjusted according to the daily intake of feed and clinical condition. At the conclusion of this first 7-day phase, circulating blood parameters were closer to the reference values and the BCS moved from 3 to 4 out of 9. Bowel motility was restored, and faecal score improved (4/8). In the second phase, allowance to pasture and a combination diet with compound mixed feed were designed. Within four weeks of starting the nutritional plan, blood parameters were re-established to reference values. The gradual feed provision calculated in this two-phase approach proved successful in support of the overall clinical improvement observed after four weeks of treatment, in a severely undernourished jenny with compromised liver functions.

Optimization of LiF dissolution with Al2(SO4)3 and its application to lithium extraction by fluorination of α-spodumene - Gustavo D. Rosales; Alexander C. Resentera; Gretel J. Fino; Eliana G. Pinna; Mario H. Rodriguez (Hydrometallurgy, 2024)

Comparing biogenic blue mussel (Mytilus edulis) reef definitions in Northern Europe: Implications for management and conservation - Julie Lydia Stounberg; Karen Timmerman; Karsten Dahl; Maurizio Pinna; Jon C. Svendsen (Environmental Science & Policy, 2024)

Use of ozonated sunflower oil in the treatment of infectious endometritis in mares - Naiane F Oliveira; Camila S Ferreira; Luis F Silva; Isadora P Santos; Julio C Jacob; Bruno A Penna; Aline E Pinna (Journal of Equine Veterinary Science, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Secretive fish diversity: A new species of Listrura (Siluriformes, Trichomycteridae) from a supposedly well‐known river in south‐eastern Brazil - Leandro Villa‐Verde; Mario C. C. de Pinna; Vinícius J. C. Reis; Osvaldo T. Oyakawa (Journal of Fish Biology, 2022)
The trichomycterid catfish Listrura menezesi , new species, is described from a flooded area adjacent to Rio das Panelas, Rio São João basin, Cachoeiras de Macacu municipality, Rio de Janeiro State, Brazil. It represents a most valuable remnant of Atlantic Forest biome that still resists the devastation of Brazilian coastlands. Listrura menezesi can be distinguished from its congeners, except L. boticario and L. depinnai , by the absence of a dorsal fin. It mainly differs from L. boticario and L. depinnai by a continuous midlateral dark stripe along the entire body ( vs . discontinuous) and a longitudinal row of irregular dots along the dorsal limit of the abdomen extending for nearly the entire body ( vs . only on the posterior half of the body in L. boticario and not forming a distinct row in L. depinnai ). Although the new species shares with L. boticario and L. depinnai the absence of dorsal fin, recent phylogenetic analyses show a close relationship between L. menezesi and L. macaensis , the latter having a dorsal fin. A putative apomorphic condition for this clade is presented: the abrupt widening on the mesethmoid axis starting posteriorly on the horizontal through the middle region of the autopalatine ( vs . anteriorly, on the horizontal through the anterior region of the autopalatine). Listrura menezesi comes as an addition to the ichthyofauna of the Rio São João drainage, a region extensively sampled for the past 20 years and supposedly well known. This paper also highlights the vulnerability of this species and the possibility of its disappearance in the near future.

Underground system of geoxylic species of Homalolepis Turcz. (Simaroubaceae, Sapindales) from the Brazilian Cerrado - Gladys Flavia de A. Melo-de-Pinna; Bruno Edson-Chaves; Karla Menezes-e-Vasconcelos; Renata C. C. de Lemos; Bruna Santos-da-Cruz; Marcelo Fernando Devecchi; José Rubens Pirani (Brazilian Journal of Botany, 2022)

Iterative taxonomy reveals a new species of Trichomycterus Valenciennes 1832 (Siluriformes, Trichomycteridae) widespread in Rio Doce basin: a pseudocryptic of T. immaculatus - Vinícius J. C. Reis; Sergio A. dos Santos; Marcelo R. Britto; Thaís de Assis Volpi; Mário C. C. de Pinna (Journal of Fish Biology, 2020)
This paper reports on a new species of Trichomycterus from the Rio Doce basin. Unusually for new taxa in the genus during the past few decades, the new species is not narrowly endemic but instead widely distributed in its major drainage, the Rio Doce. The species has been collected and deposited in scientific collections for some years, but has been systematically misidentified as the more abundant Trichomycterus immaculatus or, to a lesser degree, as other morphologically similar species from south‐eastern Brazil such as T. nigricans and T. pradensis . A combination of several morphological characteristics, such as vertebral number, pectoral‐fin ray counts, pigmentation pattern and barcoding distance, were iteratively used and unambiguously distinguish the new species from all congeners. The present case reveals a pattern of diversity‐discovery in which rare and narrowly endemic morphologically conspicuous species are discovered and described before visually inconspicuous taxa, even when the latter are more abundant and widespread. The morphological similarities among south‐eastern Brazilian species with a uniform dark‐grey color serve as basis for a brief discussion about the concepts of cryptic and pseudo‐cryptic species in Trichomycterus and their consequences for potentially hidden diversity in the genus.

Implementation of IUCN criteria for the definition of the Red List of Ecosystems in Italy - G. Capotorti; L. Zavattero; R. Copiz; E. Del Vico; L. Facioni; S. Bonacquisti; R. Frondoni; M. Allegrezza; F. Attorre; G. Bacchetta; E. Barni; E. Biondi; et al. (Plant Biosystems, 2020)

Seroprevalence and risk factors associated with equineleptospirosis in the metropolitan region of Salvador and Recôncavo Baiano region, Bahia state (NE Brazil) - Cândida C. Siqueira; Deborah B. M. Fraga; Adenizar D. Chagas-Junior; Daniel A. Athanazio; Marta M. N. Silva; Robson B. Cerqueira; Flávia W. da C. McBride; Melissa H. Pinna; Maria C. C. Ayres (Tropical Animal Health and Production, 2020)

A new species of Trichomycterus Valenciennes 1832 (Trichomycteridae: Siluriformes) from the Rio Doce drainage with remarkable similarities with Bullockia and a CT‐scan survey - Vinícius J. C. Reis; Mário C. C. de Pinna; Tiago C. Pessali (Journal of Fish Biology, 2019)
A new species of Trichomycterus is described from rocky and psammic sectors near the main channel of the middle and upper Rio Doce basin in Southeastern Brazil. Trichomycterus astromycterus n. sp., is distinguished from all congeners by a number of autapomorphic characters, such as the distally expanded maxilla; the short and thick mesethmoid cornua; and the elongated anterior process of the vomer. Additional characters (short barbels, large head, 33 vertebrae, ii+8 or ii+9 dorsal‐fin rays, nine dorsal‐fin pterygiophores, markedly enlarged lips, narrow caudal peduncle, bilobed caudal fin with the lower lobe longer than the upper one) also distinguish the new species from all its congeners in Southeastern Brazil and from most congeners anywhere. Examination of internal anatomy reveals that T. astromycterus shares some intriguing characteristics with the austral genus Bullockia Arratia et al ., 1978. However, the phylogenetic significance of such similarities is still uncertain and will require further comparative study. For this reason, the new species is provisionally included in the all‐encompassing genus Trichomycterus . An osteological description is presented on the basis of CT‐scan imaging and cleared and stained specimens.

Cetopsis varii, a new species of whale catfish (Siluriformes: Cetopsidae) from the Meta Basin, Colombia - Vitor Pimenta Abrahão; Mario C. C. de Pinna (Journal of Fish Biology, 2018)
Cetopsis varii sp. nov. Cetopsidae (Cetopsinae) is described from the Río Meta basin in eastern Colombia, at middle portions of the Río Orinoco basin. The new species differs from congeners by a combination of features: the absence of a humeral spot, presence of eye, conical teeth on vomer and dentary and rounded posterior nares, along with details of body, dorsal and caudal‐fin pigmentation. The osteology of the new species is investigated through high‐resolution X‐ray computed tomography and cleared and stained specimens. Data thus obtained are used to code the new species for character states utilized in a previous phylogenetic analysis of Cetopsidae. Analysis of the expanded matrix shows that C. varii is the sister group to C. orinoco .

Conserving plant diversity in Europe: outcomes, criticisms and perspectives of the Habitats Directive application in Italy - G. Fenu; G. Bacchetta; V. Giacanelli; D. Gargano; C. Montagnani; S. Orsenigo; D. Cogoni; G. Rossi; F. Conti; A. Santangelo; M. S. Pinna; F. Bartolucci; et al. (Biodiversity and Conservation, 2017)

A new species of Ituglanis representing the southernmost record of the genus, with comments on phylogenetic relationships (Teleostei: Siluriformes: Trichomycteridae) - A. Datovo; M. C. C. de Pinna (Journal of Fish Biology, 2014)
Ituglanis australis new species, is described from tributaries of the Laguna dos Patos and Río Uruguay, in Brazil and Uruguay. This represents the southernmost record of the genus and the first occurrence of a species of Ituglanis in those systems. It is distinguished from all its congeners, except Ituglanis parahybae and Ituglanis cahyensis , by its body pigmentation with three well‐defined dark brown stripes running along each flank. Ituglanis australis differs from I. parahybae and I. cahyensis in the pectoral‐ and pelvic‐fin ray counts, the pattern of the cephalic laterosensory system and the number of dorsal‐fin basal radials. The new species, as well as several other examined congeners, has the levator internus IV muscle attached to the dorsal face of the posttemporo‐supracleithrum; a condition that corroborates the inclusion of Ituglanis into a large trichomycterine clade that also includes Bullockia , Hatcheria , Scleronema and several species of Trichomycterus . Previous proposals of the affinities within Ituglanis are reviewed and, despite some advances, the phylogenetic relationships among species of the genus remain largely unknown.

Relationships between coastal sand dune properties and plant community distribution: The case of Is Arenas (Sardinia) - G. Fenu; D. Cogoni; C. Ferrara; M. S. Pinna; G. Bacchetta (Plant Biosystems, 2012)

Rediscovery and redescription of the unusual subterranean characiform Stygichthys typhlops , with notes on its life history - C. R. Moreira; M. E. Bichuette; O. T. Oyakawa; M. C. C. De Pinna; E. Trajano (Journal of Fish Biology, 2010)
The rediscovery of the enigmatic subterranean characiform Stygichthys typhlops is reported almost a half‐century after the collection of the holotype, the only specimen previously known. Thirty‐four specimens were collected in two shallow hand‐dug wells at the region of the type locality, c. 13 km south‐west of the town of Jaíba, Minas Gerais, Brazil. These specimens provide new information on the morphology of this species, and for the first time on its life history. The conservation status of S. typhlops is discussed. The species is severely threatened by habitat loss caused by exploitation of the aquifer.

Inhibition of protein kinase CK2 suppresses angiogenesis and hematopoietic stem cell recruitment to retinal neovascularization sites - A. A. Kramerov; M. Saghizadeh; S. Caballero; L. C. Shaw; S. Li Calzi; M. Bretner; M. Montenarh; L. A. Pinna; M. B. Grant; A. V. Ljubimov (Molecular and Cellular Biochemistry, 2008)

Taxonomic Impediment or Impediment to Taxonomy? A Commentary on Systematics and the Cybertaxonomic-Automation Paradigm - Marcelo R. de Carvalho; Flávio A. Bockmann; Dalton S. Amorim; Carlos Roberto F. Brandão; Mário de Vivo; José L. de Figueiredo; Heraldo A. Britski; Mário C. C. de Pinna; Naércio A. Menezes; Fernando P. L. Marques; Nelson Papavero; Eliana M. Cancello; et al. (Evolutionary Biology, 2007)

Effect of diet on the metabolic profile of ostriches (Struthio camelus var. domesticus) - F. Bovera; G. Moniello; N. De Riu; C. Di Meo; W. Pinna; A. Nizza (Tropical Animal Health and Production, 2007)

The influence of sex hormones on vascular responses in the aorta of streptozotocin-diabetic male rats - A. Cignarella; C. Bolego; C. Pinna; R. Zanardo; I. Eberini; L. Puglisi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Androgen deprivation, estrogen treatment and vascular function in male rat aorta - A. Cignarella; C. Bolego; C. Pinna; R. Zanardo; F. Nardi; V. Zancan; L. Puglisi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)